Development of potent reversible selective inhibitors of butyrylcholinesterase as fluorescent probes - Stane Pajk; Damijan Knez; Urban Košak; Maja Zorović; Xavier Brazzolotto; Nicolas Coquelle; Florian Nachon; Jacques-Philippe Colletier; Marko Živin; Jure Stojan; Stanislav Gobec (Journal of Enzyme Inhibition and Medicinal Chemistry, 2020)
Brain butyrylcholinesterase (BChE) is an attractive target for drugs designed for the treatment of Alzheimer’s disease (AD) in its advanced stages. It also potentially represents a biomarker for progression of this disease. Based on the crystal structure of previously described highly potent, reversible, and selective BChE inhibitors, we have developed the fluorescent probes that are selective towards human BChE. The most promising probes also maintain their inhibition of BChE in the low nanomolar range with high selectivity over acetylcholinesterase. Kinetic studies of probes reveal a reversible mixed inhibition mechanism, with binding of these fluorescent probes to both the free and acylated enzyme. Probes show environment-sensitive emission, and additionally, one of them also shows significant enhancement of fluorescence intensity upon binding to the active site of BChE. Finally, the crystal structures of probes in complex with human BChE are reported, which offer an excellent base for further development of this library of compounds.